Apocalypse, Revolution and Terrorism: From the Sicari to the American Revolt Against the Modern World - Kaplan, Jeffrey (Political Violence Ser, 2018)
Cover; Title; Copyright; Contents; Acknowledgments; Introduction; Part I This was then; 1 Nothing is true, everything is permitted: premodern religious terrorism; 2 America's apocalyptic literature of the radical right; Part II This is now; 3 Red Dawn is now: race vs. nation and the American election; 4 Life during wartime: active measures in the microchip era; Conclusion; Index